Generalized Difference Methods on Arbitrary Quadrilateral Networks (Journal of Computational Mathematics, 2021)
This paper considers the generalized difference methods on arbitrary networks for Poisson equations. Convergence order estimates are proved based on some a priori estimates. A supporting numerical example is provided.